How is monetary policy transmitted to the human development index? - EKOMANE, Jean Louis (Journal of Economics and Political Economy, 2022)
Abstract. Identifying the monetary policy transmission channels to the Human Development Index (HDI) is a matter of great concern for analysts and economic policy decision takers, dealing with social welfare in the less developed countries. The exploration of those transmission mechanisms, using the conventional structural Autoregressive methodology, with Cameroon data from the World Bank, Beac and UNDP, on the period from 1990 to 2015, points out that HDI reacts significantly to the monetary policy impulses in a two years delay, through two channels: the “income-consumption channel” and “credit-consumption channel”. In addition, it appears that inflation has a negative effect on the HDI. Keywords. Monetary policy, Transmission channels, Human Development Index, Cameroun, VAR, Credit, Final consumption. JEL. E52, E58, E51, E54, O15, O23, D60.